MULTIMODAL REHABILITATION TREATMENT OF PATIENTS WITH SCIATICA - Popović, Dunja; Vojnović, Larisa; Aleksandrić, Tijana; Rapajić, Maša; Knezevic, Aleksandar; Vasin, Jana (Acta medicae Medianae, 2024)
Pain radiating from the lower back to the lower limb below the knee is known as sciatica. The purpose of this research was to ascertain how patients with sciatica responded to multimodal rehabilitation therapy. Fifty-one patients with persistent sciatica receiving treatment at the Medical Rehabilitation Clinic of the Clinical Center of Vojvodina were included in the study. In addition to demographic information, we also collected scores from the Oswestry Disability Index, Central Sensitization Inventory, Fear Avoidance Component Scale, and Numerical Rating Scale. At the beginning and completion of the treatment, results were acquired. Thirty-four out of the patients, or 66.7%, were female. The stationary multimodal treatment for chronic pain took place for a period of 20.48 ± 5.89 days. After the treatment, the NRS assessed pain intensity had significantly decreased (6.49 ± 2.22 vs. 5.00 ± 2.22, t = 5.629, p < 0.001). Following the treatment, there was a substantial improvement in the average ODI score (48.75 ± 15.16 vs. 42.24 ± 14.13 (t = 4.246, p < 0.001) and FACS score (66.80 ± 14.13 vs. 62.47 ± 16.49, t = 2.086, p = 0.042). After the course of the treatment, the CSI score decreased, although this change was not statistically significant (t = 1.446, p = 0.155). Patients receiving stationary comprehensive rehabilitation treatment see improvements in their functional status, a decrease in their level of fear-induced activity avoidance, and a reduction in the severity of their pain.